Cerebrospinal fluid inflammatory markers to differentiate between neonatal bacterial meningitis and sepsis: A prospective study of diagnostic accuracy - Nina S. Groeneveld; Sabine E. Olie; Douwe H. Visser; Linde Snoek; Diederik van de Beek; Matthijs C. Brouwer; Merijn W. Bijlsma; Rolanda Baars; Ron van Beek; Vincent Bekker; Maartje van den Berg; Geert Jan Blok; et al. (International Journal of Infectious Diseases, 2024)
Objectives: We evaluated the diagnostic accuracy of cerebrospinal fluid (CSF) inflammatory markers for diagnosing bacterial meningitis in neonates with sepsis and/or meningitis. Methods: Cases were identified from a prospective multicenter study including patients aged 0-3 months with Group B Streptococcal (GBS) or Escherichia coli culture positive sepsis/meningitis. CSF CXCL10, MDC, IL-6, IL-8, IL-10, TNF- α, MIF, IL-1RA, CXCL13, IL-1β, CRP and procalcitonin concentrations were measured with Luminex technology. Results: In 61/373 patients (17%) residual CSF from the lumbar puncture was available, of whom 16 (26%) had definitive meningitis, 15 (25%) probable meningitis and 30 (49%) had sepsis. All biomarkers were detectable in CSF and showed significantly higher concentrations in definitive meningitis versus sepsis patients and six biomarkers in probable meningitis versus sepsis patients. Discrimination between definitive meningitis and sepsis was excellent for IL-1RA (area under the receiver operating characteristic curve [AUC] 0.93), TNF-α (AUC 0.92), CXCL10 (AUC 0.90), IL-1β (AUC 0.92), IL-6 (AUC 0.94), IL-10 (AUC 0.93) and a combination of IL-1RA, TNF-α, CXCL-10 and CSF leukocyte count (AUC 0.95). CSF leukocyte count remained the predictor with the highest diagnostic accuracy (AUC 0.96). Conclusion: CSF inflammatory markers can be used to differentiate between neonatal sepsis and meningitis.